Changes in diapause related gene expression pattern during early embryonic development in HCl-treated eggs of bivoltine silkworm Bombyx mori (Lepidoptera: Bombycidae) - Sasibhushan,Sirigineedi (2013)
Investigation of differential expression of diapause related genes (five metabolic, five heat shock protein and one translational regulatory) in HCl-treated (non-diapause) and untreated (diapause) eggs of B. mori during early embryogenesis (up to 48h following oviposition) revealed the up-regulation of sorbitol dehydrogenase upon HCl treatment, indicating increased glycogen synthesis for further embryonic development but, down-regulation of phosphofructo kinase gene expression after 18h of oviposition indicating an arrest of glycerol and sorbitol conversion. The expression of poly A binding protein gene expression was higher upon HCl treatment, revealing the initiation of translation. The expression levels of other genes analyzed did not vary significantly, except for Hsp90 and Hsp40, which were up-regulated on acid treatment until 18h. Thus, Sorbitoldehydrogenase and phosphofructo kinasegenes have a crucial role in diapause termination as evidenced by HCl treatment, while the other genes did not have major roles.